2015
DOI: 10.1109/ted.2015.2410292
|View full text |Cite
|
Sign up to set email alerts
|

Physics and Mitigation of Excess OFF-State Current in InGaAs Quantum-Well MOSFETs

Abstract: A number of recent reports have noted excess OFF-state leakage current (I OFF ) in scaled InGaAs quantum-well nMOSFETs. There is growing evidence that a combination of band-to-band tunneling (BTBT) and a floating-body bipolar gain effect is responsible for this. Unless this issue is effectively addressed, the scaling potential of this transistor structure will be compromised. This paper presents a detailed study of the physics of I OFF and explores I OFF reduction strategies through 2-D device simulations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…The CSDG MOSFET delivers a cylindrical capacitance between the gate and conducting material. There exists an oxide layer that acts as a dielectric material [47]. Hence, this setup constitutes a concentric cylindrical capacitor between the layers of the transistor [38,42].…”
Section: Current Modeling For Csdg Mosfetmentioning
confidence: 99%
“…The CSDG MOSFET delivers a cylindrical capacitance between the gate and conducting material. There exists an oxide layer that acts as a dielectric material [47]. Hence, this setup constitutes a concentric cylindrical capacitor between the layers of the transistor [38,42].…”
Section: Current Modeling For Csdg Mosfetmentioning
confidence: 99%
“…This is equivalent to the introduction of positive fixed charge below the channel. In floating-body transistor designs, it has been observed that positive fixed charge beneath the channel results in degraded subthreshold characteristics in short III-V MOSFETs [3], [13] and FDSOI transistors [34]. This suggests that the appropriate transistor redesign might mitigate an SCE in future InGaAs QW-MOSFETs.…”
Section: Off-state Characteristicsmentioning
confidence: 99%
“…This has enabled the fundamental device physics studies of relevance for future logic. For example, we have recently identified the band-to-band tunneling amplified by a parasitic bipolar effect as the cause of excess OFF-state leakage current at high drain bias in InGaAs MOSFETs [12], [13]. Mitigating this is an important priority for future scaled InGaAs MOSFETs [7], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Combining a high mobility channel material, such as InGaAs, with a vertical nanowire transistor geometry is particularly interesting as the VNW geometry opens the door to heterojunction engineering in the transport direction. This new design freedom, not possible in all other lateral transistor configurations, potentially offers significant advantages, such as a reduction in gate-induced drain leakage [5]. In addition, the relaxed gate length scaling that the VNW architecture enables can alleviate the direct source to drain tunneling that is prominent in InGaAs MOSFETs with ultra-scaled dimensions [6].…”
Section: Introductionmentioning
confidence: 99%